EXPRESSION OF DIALECT WORDS IN THE NOVEL "THE LAND OF JUDAISM" (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article analyzes dialectal words, morphological, lexical, and phonetic features specific to the Tashkent dialect in Murad Mansur's novel " The land of judaism ". In addition, the effective use of the Tashkent dialect and children's speech words in the literary work is described.